Crater Lake - United States. National Park Service. Division of Audiovisual Arts.; National Audiovisual Center (Washington, DC : The Division : Distributed by National Audiovisual Center, 1984)
Explores man's relationship with Crater Lake in Oregon from prehistory to the present. Examines Indian legends about the origin of the lake and contrasts the impact of the white man's westward expansion on the Indian culture that had existed in the area for thousands of years.
Title from data sheet.
Intended audience: Visitors to Crater Lake National Park.
Issued as VHS 1/2 in.
Photographer, Kevin Peer.
Keywords: Crater Lake (Or.); Crater Lake National Park (Or.)